PERBEDAAN TEKANAN DARAH SEBELUM DAN SESUDAH TERPAPAR PANAS PADA PEKERJA BAGIAN BOTTLING PROCESS PT SINAR SOSRO DELI SERDANG TAHUN 2013 - Fahrurrozi Arfad; makmur sinaga; gerry silaban (Lingkungan dan Kesehatan Kerja, 2014)
Differences between employees’ blood pressure before and after exposure to heat in The Bottling Process area at PT Sinar Sosro Deli Serdang 2013. Blood pressure can be affected by several factors, especially in the work site that is most affected by the heat factor. Measurement of blood pressure in the work site has benefit to prevent the workers in getting some health problems, such as dehydration, hypertension and other disorders. This research is a kind of pre-experimental research with One Group Pretest Posttest approach. It aims to reveal the differences of employees’ blood pressure before and after exposure to heat in The Bottling Process area at PT Sinar Sosro Deli Serdang in 2013. The sample in this research were 20 men who are all employees (total sampling) of the bottling process area which work from 08:00 a.m. to 4:00 p.m. at PT Sinar Sosro Deli Serdang. Data were collected by measuring the employees’ blood pressure and will be analyzed by using paired t-test statistics. The results showed that there was no significant differences between the employees’ systolic blood pressure after exposure to heat in The Bottling Process at PT Sinar Sosro with sig value 0.246 (p> 0,05). It also found in diastolic blood pressure. There was no significant differences between employees’ diastolic blood pressure after exposure to heat in The Bottling Process at PT Sinar Sosro with sig value 0.606 (p> 0,05). PT Sinar Sosro is expected to enhance their efforts in controlling the workplace’s heat. The prevention can be done by adding ventilations and local exhauster, provosioning rest area, water consumption system or administrative treat (job rotation). Keywords: Heat, Blood Pressure, Systolic, Diastolic